2016
DOI: 10.15376/biores.11.4.10528-10539
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Power during Cross-Cutting of Selected Wood Species with a Circular Saw

Abstract: This study assessed the effect of selected factors, such as the feed force (Ff = 15, 20, and 25 N), wood species (beech (Fagus sylvatica L.), English oak (Quercus robur L.), and spruce (Picea abies L.)), and the number of saw blade teeth (z = 24, 40, and 60) on cutting power in the cross-cutting of lumber. The cutting was done using a circular saw with a rotating motion of the saw blade at a constant cutting speed (vc) of 62 m.s -1 . The tangentially bucked lumber had a relative humidity (wr) of 12% ± 1% and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…Heisel et al (2007) specified that with increasing of feed rate, the normal and parallel force increases. Many other authors showed that the cutting force increases with feed rate (or feed force) [ 8 , 10 , 11 , 12 , 13 ]. Dippon et al (2000) [ 14 ] discussed the cutting forces during machining MDF (Medium Density Fiberboard) where the cutting force and feed force were expressed as functions of cutting speed, feed rate, cutting depth and rake angle (tool geometry) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Heisel et al (2007) specified that with increasing of feed rate, the normal and parallel force increases. Many other authors showed that the cutting force increases with feed rate (or feed force) [ 8 , 10 , 11 , 12 , 13 ]. Dippon et al (2000) [ 14 ] discussed the cutting forces during machining MDF (Medium Density Fiberboard) where the cutting force and feed force were expressed as functions of cutting speed, feed rate, cutting depth and rake angle (tool geometry) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Circular saw blade cutting is the most widely spread way of wood sawing. Owing to different design and construction of circular saw blades, it is possible to cut in different ways with respect to the wood fibers (Kminiak et al, 2016;Strelkov, 2009;Naylor et al, 2012).…”
Section: Cross-cutting Wood By Circular Saws 11 Poprečno Rezanje Drmentioning
confidence: 99%
“…The fact that the saw diameter is bigger, number of teeth more and feed speed less is very effective in terms of machining efficiency and surface roughness in selection of saw blade in the machining of high-density materials (Table 3). It is possible to increase the capacity and to obtain quality products by reducing the processing costs by selecting the appropriate tools [9,35,47,53,59]. Circular saw blade geometry is the most significant factor that effects its strength.…”
Section: Saw Blade Selection In Machining Of Wood Materials In Circulmentioning
confidence: 99%
“…Climb sawing is required more power than counter sawing in terms of cutting processes. At the same time, HSS blades have more impact on power consumption than HW and DP blades [50][51][52][53][54][55].…”
Section: Machining Conditionsmentioning
confidence: 99%